2019
DOI: 10.1096/fj.201802669rr
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of maternal choline supplementation on CA1 pyramidal neuron gene expression in the Ts65Dn mouse model of Down syndrome and Alzheimer's disease

Abstract: Choline is critical for normative function of 3 major pathways in the brain, including acetylcholine biosynthesis, being a key mediator of epigenetic regulation, and serving as the primary substrate for the phosphatidylethanolamine N‐methyltransferase pathway. Sufficient intake of dietary choline is critical for proper brain function and neurodevelopment. This is especially important for brain development during the perinatal period. Current dietary recommendations for choline intake were undertaken without cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 121 publications
(184 reference statements)
2
43
0
Order By: Relevance
“…Thirdly, there is now a well-established body of evidence from animal studies showing that higher choline intakes can ameliorate neurological damage associated with inherited conditions such as Down Syndrome, as well as potentially protecting the brain from the neuropathological changes associated with Alzheimer's Disease [43,[82][83][84][85][86]95,[106][107][108][109]137]. In particular, the scientific evidence shows that maternal choline supplementation protects basal forebrain cholinergic neurons and normalizes neurogenesis helping to improve cognition and attention in individuals with Down Syndrome, who can exhibit hallmarks of Alzheimer's Disease as early as the third decade of life [137,138].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, there is now a well-established body of evidence from animal studies showing that higher choline intakes can ameliorate neurological damage associated with inherited conditions such as Down Syndrome, as well as potentially protecting the brain from the neuropathological changes associated with Alzheimer's Disease [43,[82][83][84][85][86]95,[106][107][108][109]137]. In particular, the scientific evidence shows that maternal choline supplementation protects basal forebrain cholinergic neurons and normalizes neurogenesis helping to improve cognition and attention in individuals with Down Syndrome, who can exhibit hallmarks of Alzheimer's Disease as early as the third decade of life [137,138].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple animal studies [82][83][84][85][86][87] have observed positive effects of choline on neurogenesis, many of which have studied effects on neuron gene expression. Effects of choline on angiogenesis have also been observed.…”
Section: Brain Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, we demonstrated that rescuing protein O-GlcNAcylation levels in Ts2Cje mice by intranasal Thiamet G administration (25μg/mouse; 2 times/day for 5 days) boosted autophagy induction favoring the restoration of proteostasis [ 56 ]. Alldred and colleagues in 2019 examined the impact of perinatal maternal choline supplementation in Ts65Dn mouse to discern the effects on gene expression within adult offspring at ~6 and 11 months of age [ 224 ]. The authors found that maternal choline supplementation (5.0 g/kg choline chloride) diet produced significant changes in offspring gene expression levels associated with age-related cognitive decline including the endosomal-lysosomal pathway and autophagy.…”
Section: Targeting Stress Responses In Down Syndrome Brainmentioning
confidence: 99%
“…BFCN loss and changes in hippocampal innervation are consistently reported in Ts65Dn mice > 10 MO (26,27,29,37,38). Expression level changes in trisomic mice have been limited to regional analysis (37,39) or speci c neuronal subtype assessment by microarrays (35,(40)(41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%